Mpox and Surgery: Protocols, Precautions, and Recommendations - Nikolaos Kamaratos-Sevdalis; Islam Kourampi; Nazli Begum Ozturk; Anna C. Mavromanoli; Christos Tsagkaris (Microorganisms)
Mpox, also known as Monkeypox, is an infectious disease known to spread via direct contact and fomites, which poses a significant contagion risk in surgical settings and may increase the challenges already posed by COVID-19. Within the three years following the outbreak of Mpox, we conducted a review of the impact of Mpox on surgical practice. We searched Pubmed/Medline and Scopus, focusing on original studies and case reports in English or German. Our search terms included “Mpox”, “Monkeypox”, and “Surgery”. Out of 60 clinical or epidemiological studies, as well as expert opinions, brief reports, and pertinent literature reviews, eight were included after full-text assessment. We also incorporated two pertinent literature reviews, including a total of 10 papers, in this analysis. The main topics addressed by the literature are 1. manifestations of Mpox for surgical consideration or urgent management, for which it is important to consider whether a surgical approach is needed to address long-term Mpox-related lesions and 2. infection control in surgical settings, especially considering its impact on elective surgery and the well-being of healthcare workers. Mpox could affect surgical services and access to operating theaters. Unlike COVID-19, Mpox, compared to initial concerns, has not substantially compromised surgical delivery. However, limited reports exist on the surgical impact of Mpox. It is crucial to involve surgeons in Mpox diagnosis, educate surgical practitioners on its mimicry of common surgical conditions, enhance infection control during surgery, and ensure access to corrective surgery as a means of tackling the stigmatization associated with Mpox and sexually transmitted diseases in general.